Corporate Crime Liability: Beyond Rule Reform on Indonesia Criminal Policy - I Dewa Made Suartha; Jared Ivory (Focus Journal : Law Review, 2024)
The acceptance of the corporation as the subject of a criminal act, causing problems in the accountability of corporate criminal acts, because of the existence of vague norms that cause injustice and uncertainty in its application. In this study, there are two main problems, namely regulation of corporate criminal liability in criminal law in Indonesia and the prospect of criminal law on the liability of corporate criminal acts in Indonesia from the perspective of ius constituendum. The research method used is a normative legal research method with a statutory approach, comparison study and legal concepts analysis. The results of the study are: (1) As a vague norm in the regulation of corporations as the subject of criminal acts that can be accounted for in the Criminal Code and several laws outside the Criminal Code have regulated corporations as the subject of criminal acts that can be accounted for in criminal law, (2) The prospect of regulating corporate criminal liability in the 2019 Draft Criminal Code has completely and firmly regulated corporations as the subject of criminal acts and can be accounted for in criminal law and accepts absolute criminal liability and certain substitute criminal liability.